A 17-kDa Fragment of Lactoferrin Associates With the Termination of Inflammation and Peptides Within Promote Resolution - Lutaty, Aviv; Soboh, Soaad; Schif-Zuck, Sagie; Zeituni-Timor, Orly; Rostoker, Ran; Podolska, Malgorzata J.; Schauer, Christine; Herrmann, Martin; Muñoz, Luis E.; Ariel, Amiram (Frontiers in Immunology, 2018)
During the resolution of inflammation, macrophages engulf apoptotic polymorphonuclear cells (PMN) and can accumulate large numbers of their corpses. Here we report that resolution-phase-macrophages acquire the neutrophil-derived glycoprotein lactoferrin (Lf) and fragments thereof in vivo and ex vivo. During the onset and resolving phases of inflammation in murine peritonitis and bovine mastitis Lf fragments of 15 and 17 kDa occurred in various body fluids, and the murine fragmentation, accumulation and release were mediated initially by neutrophils, and later by efferocytic macrophages. The 17 kDa fragment contained two bioactive tripeptides, FKD and FKE that promoted resolution phase macrophage conversion to a pro-resolving phenotype. This resulted in a reduction in peritoneal macrophage numbers and an increase in the CD11blow subset of these cells. Moreover, FKE, but not FKD, peptides enhanced efferocytosis of apoptotic PMN, reduced TNFalpha and IL-6 and increased IL-10 secretion by LPS-stimulated macrophages ex vivo. In addition, FKE promoted neutrophil-mediated resolution at high concentrations (100 microM) by enhancing the formation of cytokine-scavenging aggregated NETs (tophi) at low cellular density. Thus, PMN lactoferrin is processed, acquired, and "recycled" by neutrophils and macrophages during inflammation resolution to generate fragments and peptides with paramount pro-resolving activities.